Proteomic Analysis of Silk Fibroin Reveals Diverse Biological Function of Different Degumming Processing From Different Origin - Wang, Yaling; Liang, Yunyun; Huang, Jiacen; Gao, Yisheng; Xu, Zhixin; Ni, Xuejun; Yang, Yumin; Yang, Xiaoming; Zhao, Yahong (Frontiers in Bioengineering and Biotechnology, 2022)
Silk, as a kind of natural fibrin, has been prepared into various biomaterials due to its excellent biocompatibility and mechanicalness. However, there are some controversies on the biocompatibility of silk fibroin (SF), especially when it coexists with sericin. In this study, two kinds of silk from Jiangsu and Zhejiang were degummed with two concentrations of Na2CO3 solution respectively to obtain four kinds of silk fibroin. The effects of different degumming treatments on silk fibroin properties were analyzed by means of color reaction, apparent viscosity measurement, transmission electron microscope and iTRAQ analysis, and the effects of different silk fibroin membranes on the growth of Schwann cells were evaluated. The results showed that the natural silk from Zhejiang and treated with 0.05% Na2CO3 solution had fuller structure, higher apparent viscosity and better protein composition. While SF obtained by degumming with 0.5% Na2CO3 solution was more beneficial to cell adhesion and proliferation due to thorough removal of sericin. This study may provide important theoretical and experimental basis for the selection of biomaterials for fabricating artificial nerve grafts.